Shaping the future of child and adolescent mental health : towards technological advances and service innovations - Hodes, Matthew; De Vries, Petrus J. (Academic Press, 2023)
Shaping the Future of Child and Adolescent Mental Health: Towards Technological Advances and Service Innovations coincides with the 25th International Association for Child and Adolescent Psychiatry and Allied Professions (IACAPAP) Congress in Dubai from December 5-9, 2022. There are three overarching themes of this book. Firstly, the impact of the Internet and digital technologies on the mental health and well-being of children and adolescents, including computerized therapies, and the fundamental role of technologies to advance knowledge in the field. Secondly, a theme on harnessing the expansion of knowledge on psychiatric disorders and their treatment for children and adolescents, exemplified by chapters on different kinds of adversity in child and adolescent mental health and a chapter on precision therapeutics. Given the location of the IACAPAP Congress, the third theme focuses on aspects of child and adolescent mental health in the Eastern Mediterranean Region. Chapters provide insights into a broad range of contemporary technology- and service innovation-related topics in child and adolescent psychiatry and mental health. These include growing up in the digital age, cyberbullying, clinical applications of big data and machine learning, computerized cognitive behavioral therapy, technology- enhanced learning, lessons from COVID-19, new understanding of the consequences of psychological trauma, autoimmune encephalitis, and precision therapeutics in depression. Acknowledging the global challenge of child and adolescent psychiatry and mental health, readers will find an emphasis on contextual challenges in the field, including innovations for scaling up of mental health intervention in low- and middle-income countries, and research and training in the Eastern Mediterranean Region.